Capital Increment Trend of Nepal Multipurpose Cooperatives Society - Uprety, Bikash Prasad (Kanakai Journal, 2022)
This study aims to analyze the capital increment trend of Nepal Multipurpose Cooperatives Society (NMC) in the last 9 years. NMC was established on 8March 1994 as a cooperative organization. This article reciprocally analyses the changing situation of its capital and number of members during ten years. NMC is an autonomous institution. However, its financial activities and positions are not independent. They depend on various external financial factors, i.e., the overall changing in the capital scenario of Nepal's Capital Market, level of competition among financial institutions, recent trends of capital situations in its internal affairs, government policy towards cooperatives, general attitudes of people and some internal movement regarding its operational activities. Basically, growth of a cooperative organization depends upon the managerial skills and responsible authorities of a cooperative organization and some crucial external factors which directly or indirectly affect the institutional activities. The increasing trend of capital and number of shareholder members indicate the increasing volume of the institution which shows NMC is a growing organization. Mainly, share capital, institutional capital, number of shareholder members, per member average share capital profitability as a form of earning per share are analyzed in this article. Capital increment trend is also analyzed with the eight years' strategic business plan.